Carbon nanotube/reduced graphene oxide hybrid for simultaneously enhancing the thermal conductivity and mechanical properties of styrene -butadiene rubber. (October 2017) - Song, Shiqiang; Zhang, Yong
Abstract: A novel hybrid of polymer functionalized-carbon nanotube @ reduced graphene oxide (PCNT@RGO) was prepared by reversible addition-fragmentation chain transfer polymerization, esterification reaction and reduction process. PCNT@RGO hybrid as a filler can effectively enhance the thermal conductivity and mechanical properties of styrene-butadiene rubber (SBR) vulcanizate. Remarkably, the tensile strength and stress at 200% extension of the SBR vulcanizate reached as high as 8.8 and 7.7 MPa at PCNT@RGO loading of 3 wt%, increasing by approaching 203% and 450% compared with neat SBR. Furthermore, the vulcanizate also exhibited high thermal conductivity (0.45 W/m K), which is 2.0-fold higher than that of SBR. The improvement in properties could be attributed to the synergetic effect of PCNT and RGO in PCNT@RGO hybrid, strong interfacial between PCNT@RGO and SBR matrix, the large constrained regions and continuous filler networks. Such good performances render the SBR/PCNR@RGO composite appealing for the use in various engineering practices. Graphical abstract: